Studies on immunity in the male genital tract - Olivier, Abraham Jacobus (Division of Virology, 2015)
The male genital tract is a major site of HIV acquisition and transmission. It is an obvious site for inducing immune responses to candidate HIV vaccines, to prevent infection or halt the spread of the virus. There are relatively few published studies characterising T cells in the male genital tract. A challenge that hampers studies at this mucosal surface is obtaining samples with sufficient immune cells. Therefore, the first aim of this study was to establish an optimised method to isolate immune cells from the male genital tract. Cellular activation and inflammation in the genital tract have important implications for both transmission and acquisition of HIV, since they provide target cells for viral replication. Thus, the second and third aim of this study was to investigate mucosal T cell activation and inflammatory cytokine profiles in semen in HIV?infected and uninfected men, and compare the immune milieu of the genital tract with the systemic compartment.